Case Report: Ehrlichia ewingii Infection in a Shih Tzu Mix Dog - Nazara, Nonitema; Jayanti, Putu Devi; Suartha, I Nyoman (Media Kedokteran Hewan, 2024)
Ehrlichiosis is a dog disease caused by Ehrlichia, a gram-negative intracellular bacterium, and transmitted by ticks of the genus Rhipicephalus sanguineus. This case report aims to identify the infectious agent and describe the treatment for a case of ehrlichiosis. The examination results showed signs of ehrlichiosis in a male shih tzu mix dog aged three months. The dog had been suffering from itching, weakness, decreased appetite, and tick infestations over the entire body for the past month. The physical examination showed that the dog was limping and had pale oral mucosa. Meanwhile, the routine hematological examination showed signs of neutrophilia, hypochromic microcytic anemia, and thrombocytopenia. In addition, the blood smear examination showed intracytoplasmic bodies in the neutrophils of the dog. Blood tests using the test kit showed a positive result for ehrlichiosis. The dog was diagnosed with ehrlichiosis with a good prognosis. The treatment included doxycycline at a dose of 10 mg/kg BW q24h PO for 28 days, Livron B.plex at a dose of 1 tablet per day PO for 14 days, Fufang Ejiao Jiang at a dose of 1 ml per day PO for 14 days, and Bravecto Spot-on. The condition of the dog improved after seven days of treatment. However, the routine hematological examination on day seven still showed signs of anemia and thrombocytopenia, necessitating continued supportive drugs.